Enhancing ZnO-NP Antibacterial and Osteogenesis Properties in Orthopedic Applications: A Review - Li Y (Dove Medical Press, 2020)
Yuehong Li,1 Yue Yang,2 Yun’an Qing,1 Ruiyan Li,1 Xiongfeng Tang,1 Deming Guo,1 Yanguo Qin1 1Orthopaedic Medical Center, The Second Hospital of Jilin University, Changchun, People’s Republic of China; 2Department of Cardiology, China-Japan Union Hospital of Jilin University, Changchun, People’s Republic of ChinaCorrespondence: Yanguo Qin Email qinyg@jlu.edu.cnAbstract: Prosthesis-associated infections and aseptic loosening are major causes of implant failure. There is an urgent need to improve the antibacterial ability and osseointegration of orthopedic implants. Zinc oxide nanoparticles (ZnO-NPs) are a common type of zinc-containing metal oxide nanoparticles that have been widely studied in many fields, such as food packaging, pollution treatment, and biomedicine. The ZnO-NPs have low toxicity and good biological functions, as well as antibacterial, anticancer, and osteogenic capabilities. Furthermore, ZnO-NPs can be easily obtained through various methods. Among them, green preparation methods can improve the bioactivity of ZnO-NPs and strengthen their potential application in the biological field. This review discusses the antibacterial abilities of ZnO-NPs, including mechanisms and influencing factors. The toxicity and shortcomings of anticancer applications are summarized. Furthermore, osteogenic mechanisms and synergy with other materials are introduced. Green preparation methods are also briefly reviewed.Keywords: antibacterial property, composite material, orthopedic implant, osteogenic activity, zinc oxide nanoparticles